It's just not cricket : a case of ethics, integrity, and organizational culture within a national sport governing body - Ingerson, Lynley; Naraine, Michael L. (London : Human Kinetics, Inc., 2019)
In early 2018, Cricket Australia, the national governing body for cricket in Australia, experienced a critical incident when men's national test athletes were caught in a ball tampering scandal known as ‶Sandpaper-gate." As the ‶custodians of the game," integrity and culture are extremely important, and the incident was the catalyst for the organization to hire a new Integrity Manager. This case study concentrates on the story of Patrick Murphy, the new, fictitious hire at Cricket Australia tasked with helping to rebuild the organization's ethical culture. After learning of Patrick's past sport experiences, the narrative reveals additional non-fictitious elements that have emanated over the course of the past few years, which are affecting the organization's present culture. After learning about the doping, human resource management, sex and diversity, and athlete management issues, Patrick is tasked with performing a culture audit and reporting back to his superiors. This case study offers a contemporary context in which to discuss ethics and culture in sport, notably from a large, non-North American sport organization.
Originally Published InIngerson, L., & Naraine, M. (2019). It's Just Not Cricket: A Case of Ethics, Integrity, and Organizational Culture Within a National Sport Governing Body. Case Studies in Sport Management, 8(S1), S1-S6.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Sports -- Moral and ethical aspects; Corporate culture; Cricket -- Rules